Convergence Theorem for Nonexpansive Semigroups in \(q\)-Uniformly Smooth Banach Spaces - Witthayarat, Uamporn; Wattanawitoon, Kriengsak (Communications in Mathematics and Applications, 2019)
In this paper, we present the iterative scheme nonexpansive semigroups in the framework of \(q\)-uniformly smooth and uniformly convex Banach spaces. Furthermore, we propose the strong convergence theorem for finding fixed points problem of nonexpansive semigroups under some appropriate conditions. Our results extend the recent ones of some authors.